Ojibwe and Cree materials, Daythal L. Kendall Papers - Kendall, Daythal; Voorhis, Paul H.; Merriam, Kathryn Lavely (1970)
After finishing his PhD, Daythal Kendall accepting a position at Brandon University, Manitoba to teach local varieties of Cree and Ojibwe, as a temporary replacement for Paul Voorhis. He therefore possessed a large number of Paul Voorhis' Cree publications (Series 5), and during this time produced a large volume of lessons to teach Canadian Aboriginal syllabics. These are in various forms in Series 3, including students' exercises. There is also correspondence relating to this period with Paul Voorhis and Katherine Merriam, as well as a separate conversation relating to American Philosophical Society materials (Series 1)